2014
DOI: 10.1128/aac.02615-13
|View full text |Cite
|
Sign up to set email alerts
|

Multilaboratory Study of Epidemiological Cutoff Values for Detection of Resistance in Eight Candida Species to Fluconazole, Posaconazole, and Voriconazole

Abstract: uAlthough epidemiological cutoff values (ECVs) have been established for Candida spp. and the triazoles, they are based on MIC data from a single laboratory. We have established ECVs for eight Candida species and fluconazole, posaconazole, and voriconazole based on wild-type (WT) MIC distributions for isolates of C. albicans (n ‫؍‬ 11,241 isolates), C. glabrata (7,538), C. parapsilosis (6,023), C. tropicalis (3,748), C. krusei (1,073), C. lusitaniae (574), C. guilliermondii (373), and C. dubliniensis (162). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
62
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 39 publications
6
62
0
3
Order By: Relevance
“…This provides further support for the concept that posaconazole ECVs for C. krusei and other common species of Candida may be set too low, perhaps because the ECVs were derived from MIC distributions which were obtained from a single laboratory (30). However, ECVs for MIC distributions originating from Ն6 laboratories for posaconazole remained substantially unchanged for eight species of Candida, including C. albicans, C. tropicalis, and C. krusei (46).…”
Section: Resultsmentioning
confidence: 72%
“…This provides further support for the concept that posaconazole ECVs for C. krusei and other common species of Candida may be set too low, perhaps because the ECVs were derived from MIC distributions which were obtained from a single laboratory (30). However, ECVs for MIC distributions originating from Ն6 laboratories for posaconazole remained substantially unchanged for eight species of Candida, including C. albicans, C. tropicalis, and C. krusei (46).…”
Section: Resultsmentioning
confidence: 72%
“…Since the SYO panel also provides MICs for the other two echinocandins, SYO ECVs for anidulafungin and micafungin would be useful for laboratories using this method. The ECV is the highest endpoint of the MIC distribution of the wild-type (WT) population and is established using MIC distributions from multiple laboratories (at least 3 laboratories and 100 MICs/species/agent) (13,16,17). ECV surveillance may detect the emergence of in vitro resistance or distinguish between phenotypic WT isolates (isolates with no detectable phenotypic resistance) and non-WT isolates (isolates with mechanisms of resistance) (13,(16)(17)(18).…”
mentioning
confidence: 99%
“…All isolates of C. krusei are considered to be R to fluconazole, irrespective of the MIC. Because of the lack of CBPs for the less common species of Candida and C. neoformans (14), the ECVs of fluconazole were used for C. lusitaniae (1 g/ml), C. dubliniensis (0.5 g/ml), C. guilliermondii (8 g/ ml), C. pelliculosa (4 g/ml), C. kefyr (1 g/ml), and C. neoformans (16 g/ml) to categorize isolates of these species as wild type (WT; MIC, ՅECV) or non-WT (MIC, ϾECV) (11,12,14). VME were identified when the reference CLSI BMD MIC indicated an R or non-WT result and the Vitek 2 MIC was S or WT.…”
Section: Studymentioning
confidence: 99%
“…Several studies have demonstrated excellent essential agreement (EA; within 2 dilutions) and categorical agreement (CA; susceptibility results that fall within the same interpretive category) between the Vitek 2 and CLSI BMD methods for testing fluconazole against Candida species and C. neoformans (4-9). All of these studies were performed prior to the adoption by the CLSI of new (lower), species-specific clinical breakpoints (CBPs) and epidemiological cutoff values (ECVs) of fluconazole for several species of Candida and C. neoformans (10)(11)(12)(13)(14). Pfaller et al (15) reanalyzed the original data from a previous study (7) by using the new CBPs and ECVs of fluconazole and found that the CA between the Vitek 2 and CLSI BMD methods was 96.8% with no very major errors (VME) and only 1.3% major errors (ME) (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation